MPOX OUTBREAK INVESTIGATION AMONG HIV-POSITIVE PATIENTS IN YOGYAKARTA CITY, INDONESIA, 2024 (Proceedings of the Global Public Health Conference, 2025)
In July 2022, WHO declared mpox as a Public Health Emergency of International Concern (PHEIC) due to its rapid spread and caused outbreaks worldwide. In December 2023, an outbreak of mpox infections occurred in Yogyakarta City. The investigation aimed to explore sociodemographic and risk factors of the outbreak -and recommend control measures. A descriptive study was conducted from December 6, 2023, to March 2, 2024. Active case finding through direct interviews with the cases followed by contact tracing. Cases defined as individuals presenting with skin rashes include single or multiple lesions on the anogenital area or other areas of the body, for which the rash is not caused by other diseases and confirmed through diagnostic tests using Polymerase Chain Reaction (PCR). Two confirmed cases of mpox were found without an epidemiological link with zero death. Both cases were 35 and 34 years-old males with a history of HIV-positive under regular ARV treatment, experiencing fever, lesions, anogenital pain, fatigue, and diarrhea. One of them had syphilis (50%). Risk factors include sexual orientation as a man who has sex with men (MSM) and bisexual, with no history of travelling abroad. During treatment, they were instructed to self-isolation along with close contacts, including sexual partners. There has been local transmission of mpox in Yogyakarta City, especially among key populations. Health authorities should increase awareness, enhance surveillance, case detection and health promotion to limit the spread of the disease.
Keywords: mpox; zoonosis; outbreak; HIV